Conceptualizing Relevance of Information as a Social Justice Issue: An Interactive Panel Discussion. Issue 1 (13th October 2021) - Winberry, Joseph; Gray, LaVerne; Hardy, Jean; Jaber, Baheya; Mehra, Bharat
Abstract: Relevance is a notion whose meaning and purpose have been widely discussed in information retrieval research. The ultimate aim of relevance—what Tefko Saracevic has called the "you know" principle—is to ensure that users have the information necessary to meet their goals. What is often missing from this discussion is a critical assessment of who gets to decide what information is relevant, under what circumstances, and for what purposes—especially in relation to marginalized populations. The limited discussion of social justice in information relevance research is a gap this interactive panel discussion seeks to address. Five emerging, junior, and senior researchers will each identify and outline social justice themes of information relevance (e.g., intersectionality, Black feminist lens, geography, immigration status, and holistic critical relevance) that have been evident in their own scholarship. Audience members will have an opportunity to expand on one of the five themes in concert with a panelist before participants consider together future directions for relevance of information in a social justice context. While each participant may have different definitions of social justice, a broad interpretation of the term will frame the conversation by indicating how information relevance can move society towards a fairer and more equitable future.